Konflik Sosial Jemaat Gereja Masehi Injili di Halmahera Pasca Pemilihan Gubernur Maluku Utara - Labobar, Maichel Seivo (JURNAL ILMIAH SOCIETY, 2015)
Indonesia adopts a democratic system inÂ goverment. Some issue from useing democracy system in Indonesia which is the Regional Heads Electing (Direct electing). AlthoughÂ Religion was aÂ vehicle to achieve purpose of theseÂ groups. Purpose to analizingÂ the occuredÂ from the impact of Internal ConflictÂ in Evangelican Christian Church in 2013. The result of this research indicate social conflict inÂ Evangelican Christian Church post North Maluku Governors electingÂ in 2013, explicity and clearly commited by BPHS result in dorumeÂ that GMIH reform movement arose by elments of regional heads who lost in governor direct electing battle in North Maluku with utilised constituent to breakdown the solidarity in GMIH life. The suggestion of this research would give an impact toward church organisation included the pastors and church commitee should not engage intoÂ practically politics activity or become politics commitee. Pastors who had structurally ocuppation should not involved inÂ the pratical politics ( take care the Party, to be a candidate of Council, KPU, and Regent /Vise Regent, Governor/Vise Governor). Local Goverment in this case North Halmahera Regent and Local Citizen Council Delegation (DPRD) must quick respons to watch Church complication problems and find out the right solution. Keywords : Social Conflict, The Governorâs Election, Democracy